Parthenocarpy-related genes induced by naphthalene acetic acid in oil palm interspecific O × G [Elaeis oleifera (Kunth) Cortés × Elaeis guineensis Jacq.] hybrids - Montoya, Carmenza; Mejia-Alvarado, Fernan Santiago; Botero-Rozo, David; Ayala-Diaz, Ivan Mauricio; Romero, Hernan Mauricio (Frontiers in Genetics, 2023)
Parthenocarpy is the development without fertilization of seedless fruits. In the oil palm industry, the development of parthenocarpic fruits is considered an attractive option to increase palm oil production. Previous studies have shown the application of synthetic auxins in Elaeis guineensis, and interspecific O×G hybrids (Elaeis oleifera (Kunth) Cortés × E. guineensis Jacq.) induces parthenocarpy. The aim of this study was to identify the molecular mechanism through transcriptomics and biology system approach to responding to how the application of NAA induces parthenocarpic fruits in oil palm O×G hybrids. The transcriptome changes were studied in three phenological stages (PS) of the inflorescences: i) PS 603, pre-anthesis III, ii) PS 607, anthesis, and iii) PS 700, fertilized female flower. Each PS was treated with NAA, Pollen, and control (any application). The expression profile was studied at three separate times: five minutes (T0), 24 hours (T1), and 48 h post-treatment (T2). The RNA sequencing (RNA seq) approach was used with 27 oil palm O×G hybrids for a total of 81 raw samples. RNA-Seq showed around 445,920 genes. Numerous differentially expressed genes (DEGs) were involved in pollination, flowering, seed development, hormone biosynthesis, and signal transduction. The expression of the most relevant transcription factors (TF) families was variable and dependent on the stage and time post-treatment. In general, NAA treatment expressed differentially more genes than Pollen. Indeed, the gene co-expression network of Pollen was built with fewer nodes than the NAA treatment. The transcriptional profiles of Auxin-responsive protein and Gibberellin-regulated genes involved in parthenocarpy phenomena agreed with those previously reported in other species. The expression of 13 DEGs was validated by RT-qPCR analysis. This detailed knowledge about the molecular mechanisms involved in parthenocarpy could be used to facilitate the future development of genome editing techniques that enable the production of parthenocarpic O×G hybrid cultivars without growth regulator application.